Concurrent nanoscale surface etching and SnO2 loading of carbon fibers for vanadium ion redox enhancement - Maruyama, Jun; Maruyama, Shohei; Fukuhara, Tomoko; Nagaoka, Toru; Hanafusa, Kei (Beilstein Journal of Nanotechnology, 2019)
Facile and efficient methods to prepare active electrodes for redox reactions of electrolyte ions are required to produce efficient and low-cost redox flow batteries (RFBs). Carbon-fiber electrodes are widely used in various types of RFBs and surface oxidation is commonly performed to enhance the redox reactions, although it is not necessarily efficient. Quite recently, a technique for nanoscale and uniform surface etching of the carbon fiber surface was developed and a significant enhancement of the negative electrode reaction of vanadium redox flow batteries was attained, although the enhancement was limited to the positive electrode reaction. In this study, we attempted to obtain an additional enhancement effect of metal-oxide nanoparticles without the need for further processing steps. A coating with carbonaceous thin films was obtained coating by sublimation, deposition, and pyrolysis of tin(II) phthalocyanine (SnPc) on a carbon fiber surface in a single heat-treatment step. The subsequent thermal oxidation concurrently achieved nanoscale surface etching and loading with SnO2 nanoparticles. The nanoscale-etched and SnO2-loaded surface was characterized by field-emission scanning electron microscopy (FESEM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The activity for the vanadium ion redox reactions was evaluated by cyclic voltammetry (CV) to demonstrate the enhancement of both the positive and negative electrode reactions. A full cell test of the vanadium redox flow battery (VRFB) showed a significant decrease of the overpotential and a stable cycling performance. A facile and efficient technique based on the nanoscale processing of the carbon fiber surface was presented to substantially enhance the activity for the redox reactions in redox flow batteries.
Keywords: carbon fiber; electrode reactions; metal-oxide nanoparticles; redox flow batteries; surface etching

(untitled) - Friedl, J.; Lebedeva, M. A.; Porfyrakis, K.; Stimming, U.; Chamberlain, T. W. (J. Am. Chem. Soc., 2018)

(untitled) - Winsberg, J.; Hagemann, T.; Janoschka, T.; Hager, M. D.; Schubert, U. S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Leung, P.; Shah, A. A.; Sanz, L.; Flox, C.; Morante, J. R.; Xu, Q.; Mohamed, M. R.; Ponce de León, C.; Walsh, F. C. (J. Power Sources, 2017)

(untitled) - Noack, J.; Roznyatovskaya, N.; Herr, T.; Fischer, P. (Angew. Chem., Int. Ed., 2015)

(untitled) - Gattrell, M.; Park, J.; MacDougall, B.; Apte, J.; McCarthy, S.; Wu, C. W. (J. Electrochem. Soc., 2004)

(untitled) - Sun, C.-N.; Delnick, F. M.; Aaron, D. S.; Papandrew, A. B.; Mench, M. M.; Zawodzinski, T. A. (ECS Electrochem. Lett., 2013)

(untitled) - Pezeshki, A. M.; Clement, J. T.; Veith, G. M.; Zawodzinski, T. A.; Mench, M. M. (J. Power Sources, 2015)

(untitled) - Sun, B.; Skyllas-Kazacos, M. (Electrochim. Acta, 1992)

(untitled) - Agar, E.; Dennison, C. R.; Knehr, K. W.; Kumbur, E. C. (J. Power Sources, 2013)

(untitled) - Kim, K. J.; Lee, S.-W.; Yim, T.; Kim, J.-G.; Choi, J. W.; Kim, J. H.; Park, M.-S.; Kim, Y.-J. (Sci. Rep., 2014)

(untitled) - Sun, B.; Skyllas-Kazacos, M. (Electrochim. Acta, 1992)

(untitled) - Yue, L.; Li, W.; Sun, F.; Zhao, L.; Xing, L. (Carbon, 2010)

(untitled) - Maruyama, J.; Hasegawa, T.; Iwasaki, S.; Fukuhara, T.; Nogami, M. (J. Electrochem. Soc., 2013)

(untitled) - Zhang, W.; Xi, J.; Li, Z.; Zhou, H.; Liu, L.; Wu, Z.; Qiu, X. (Electrochim. Acta, 2013)

(untitled) - Maruyama, J.; Maruyama, S.; Fukuhara, T.; Hanafusa, K. (J. Phys. Chem. C, 2017)

(untitled) - Bayeh, A. W.; Kabtamu, D. M.; Chang, Y.-C.; Chen, G.-C.; Chen, H.-Y.; Lin, G.-Y.; Liu, T.-R.; Wondimu, T. H.; Wang, K.-C.; Wang, C.-H. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Zhou, H.; Shen, Y.; Xi, J.; Qiu, X.; Chen, L. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Li, B.; Gu, M.; Nie, Z.; Wei, X.; Wang, C.; Sprenkle, V.; Wang, W. (Nano Lett., 2014)

(untitled) - Takasaki, F.; Matsuie, S.; Takabatake, Y.; Noda, Z.; Hayashi, A.; Shiratori, Y.; Ito, K.; Sasaki, K. (J. Electrochem. Soc., 2011)

(untitled) - Maruyama, J.; Shinagawa, T.; Siroma, Z.; Mineshige, A. (Electrochem. Commun., 2011)

(untitled) - Sadezky, A.; Muckenhuber, H.; Grothe, H.; Niessner, R.; Pöschl, U. (Carbon, 2005)

(untitled) - Jaouen, F.; Charreteur, F.; Dodelet, J. P. (J. Electrochem. Soc., 2006)

(untitled) - Maruyama, J.; Shinagawa, T.; Hayashida, A.; Matsuo, Y.; Nishihara, H.; Kyotani, T. (ChemElectroChem, 2016)

(untitled) - Zhang, C.; Li, L.; Ju, J.; Chen, W. (Electrochim. Acta, 2016)

(untitled) - Song, H.; Zhang, L.; He, C.; Qu, Y.; Tian, Y.; Lv, Y. (J. Mater. Chem., 2011)

(untitled) - Wang, Y.; Djerdj, I.; Smarsly, B.; Antonietti, M. (Chem. Mater., 2009)

(untitled) - Shemet, V. Z.; Pomytkin, A. P.; Neshpor, V. S. (Carbon, 1993)

(untitled) - Randin, J.-P.; Yeager, E. (J. Electrochem. Soc., 1971)

(untitled) - Fink, H.; Friedl, J.; Stimming, U. (J. Phys. Chem. C, 2016)

(untitled) - Goulet, M.-A.; Skyllas-Kazacos, M.; Kjeang, E. (Carbon, 2016)

(untitled) - Liu, Q. H.; Grim, G. M.; Papandrew, A. B.; Turhan, A.; Zawodzinski, T. A.; Mench, M. M. (J. Electrochem. Soc., 2012)